Кластерный анализ как метод содержательного сравнения схожести проектов - Чимшир, В. И. (НТУ "ХПИ", 2011)
Предложено использование кластерного анализа для содержательного сравнения схожести проектов. На основе данного подхода возможно проведение сравнительного анализа параметров проектов в случае, когда показатели имеют разнообразный вид. В результате предложенного анализа получена количественная оценка содержательной схожести проектов.

In this article there was proposed the way of cluster analysis usage for a meaningful comparison of the projects similarity. Based on this approach it becomes possible to conduct a comparative analysis of the parameters in cases when different values have a varied form, which are making it difficult to use in the traditional metric approach. As result, the proposed analysis is able to provide the quantitative assessment of the similarity between the projects.
Keywords: типовые проекты; содержательная схожесть; жизненный цикл; анализ параметров проектов; projec; standard project; cluster analysis; content similarity; life cycle